SEGMEN FEATURE DALAM PROGRAM BERITA JAWA TENGAH HARI INI DI TVRI JAWA TENGAH - Anis Kamila; Muhammad Bayu Widagdo (Interaksi Online, 2021)
Television is the most consumed media because it can reach the wider community. The development of technology encourages television to provide interesting shows in order to survive. TVRI as national television in 2019 launched an innovation in the form of rebranding to reach the millennial generation. The feature news gegment is one of the rebranding efforts carried out by TVRI Central Java. This segment is a thesis project by a group of Communication Science students at Diponegoro University with 48 segments of 3-5 minute long news packages that are broadcast in the last segment of the Jawa Tengah Hari Ini on TVRI Jawa Tengah. This segment contains about culinary, tourism, and hobbies / communities in Central Java. During the production process every person in this project has a role as producer, reporter, scriptwriter, dubber (voice over), cameraman, and video editor. During the production process, technical and non technical obstacles are inevitable, Covid19 pandemic causes production should be adjust to the situation and conditions. The Feature Wews Segment airs 27th July 2020 until 2nd November 2020 at 16:00 - 17:00 WIB. With interesting content, this segment try to reach the millennial generation by presenting informative, educational and entertaining shows.